Age dynamics of bone mineral density and of morphometric data in the lumbar spine by results of densitometrical research - I. G. Pashkova; L. A. Alexina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Morphometric parameters and the mineral density of lumbar spine were studied in 929 people (740 women and 189 men) aged 20 - 87 years, living in Karelia. The mineral density of bone was estimated by a method of a two-power x-ray absorptiometriy. The maximum decrease in a mineralization is revealed in the second lumbar vertebra. Decrease in mineral density was accompanied by increase in width of vertebra more at men than at women.